SISTEM KENDALI JARAK JAUH INTENSITAS CAHAYA LAMPU PIJAR - , ERWIN PRAWIRA S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lamp Dimmer circuit is a device that produces light in stages where the stage determines the brightness of the light, the higher the stage, the brighter the light to move. To find out the characteristics of each circuit used in the circuit's Lamp Dimmer is necessary to have a theory that can help make a circuit to work properly, so that maximum results can. Dimmers are also used as the equipment used set dim incandescent light. The arrangement is done by changing the voltage rms. This tool enables users to control even though being away from the area of equipment to be controlled, increasing the efficiency of user activity time, because this tool uses a remote control that uses ASK (Amplitude Shift Keying).